Capital Requirements and Financial Performance of Deposit Taking Sacco’s in Kenya - Maina, Dennis Moogi; Miroga, Julius (International Journal of Finance, 2025)
Purpose: The primary objective of this study was to investigate the relationship between capital requirements and the financial performance of deposit-taking savings and credit cooperative organizations in Kenya. The study was anchored on three theories: the pecking order theory, signaling theory, and liquidity management theory. Methodology: A descriptive study design was adopted for this study. The target population comprised of 176 DT-Saccos registered and licensed by the SASRA to operate in Kenya. The study used stratified random sampling to determine the target population. The study further employed Nassiuma's formula to get the sample size of 64. Data was collected through self-administered structured and semi structured questionnaires. The respondents comprised of Sacco management accounts, Sacco management officers and senior managers. The Statistical Package for Social Science was then used to examine the data that had been gathered (SPSS Version 28). Findings: The study found that capital adequacy, asset quality, earning rating, and liquidity management significantly impacted DT Saccos's financial performance. Unique Contribution to Theory, Policy and Practice: The analysis, which employed both descriptive and inferential approaches, revealed that the study had important policy implications, educating regulators and decision-makers about the sufficiency of capital requirements and their effect on the stability and expansion of Sacco's. This study assessed financial stability of Sacco’s, their impact on members and their general operational efficiency. The study was further found to contribute to the academic understanding of Sacco’s financial performance with practical applications for adoption by Sacco management. Additionally, the results of this study were also found relevant to the members of the public including current and potential Sacco members will find the study useful.